Self-assembly and label-free fluorescent aptasensor based on deoxyribonucleic acid intercalated dyes for detecting lactoferrin in milk powder - Liu, Jiahui; Li, Tengfei; Qin, Hongwei; Li, Linsen; Yan, Mengmeng; Zhu, Chao; Qu, Feng; Abd El-Aty, A. M. (Frontiers in Nutrition, 2022)
Lactoferrin (Lf), an iron-binding glycoprotein, regulates the immune system. It has broad-spectrum antimicrobial activity and is critical for child physical growth and development. As a common additive in the dairy industry, it is crucial to quantify LF content. This study established a self-assembly and universal fluorescence aptasensor for detecting LF in milk powder based on structure-selective dyes of PicoGreen intercalated in the label-free aptamer. Herein, the aptamer functions as both a specific recognition element against targets and a fluorescent signal reporter integrated with structure-selective dyes. First, the aptamer folds into a three-dimensional spatial structure based on complementary base pairings and intermolecular weak noncovalent interactions. Then, the dye is intercalated into the minor groove structures of the aptamer and triggers its potential fluorescent property. When the target exists, the aptamer binds to it preferentially, and its space structure unfolds. This causes the freeing of the subsequent dye and decreases the corresponding fluorescence. Hence, the reflected fluorescence signals could directly determine the target concentrations. Under the optimum conditions, a good linear relationship (R2, 0.980) was obtained in the Lf range from 20 to 500 nM with a detection limit of 3 nM (2.4 mg/kg) and good specificity, as well as a reliable recovery of 95.8-105.1% in milk powder. In addition, the universality was also confirmed witha good performance by quickly changing the aptamers against other targets (chlorpyrifos, acetamiprid, bovine thyroglobulin, and human transferrin) or utilizing another fluorescence dye. Therefore, this self-assembly aptasensor provides a universal and concise strategy for effective detection.